Regional split and local government spending efficiency in Indonesia - Roosemarina Anggraini Rambe; Armida S Alisjahbana; Kodrat Wibowo; Bagdja Muljarijadi (Economics, Management and Sustainability)
The research objectives are to (1) measure the efficiency of local governments in every province in Indonesia and (2) analyse the impact of regional splitting, GRDP per capita, population density, and fiscal capacity on the efficiency of local governments. This study employed per capita personnel spending, per capita spending on goods and services, and per capita capital spending. The output used in the dataset is the human development index. The first objective (local government efficiency) is measured by Data Envelopment Analysis (DEA), with VRS and an output-oriented model. DMUs are 34 provinces from 2013-to 2018. The second objective (the impact of regional splitting, GRDP per capita, population density, and fiscal capacity on efficiency) is measured by panel data regression with a random effect model. Results show that the always efficient provinces for 2013-2018 were Jakarta, Yogyakarta, and Banten. The study revealed 29 inefficient provinces in 2013, and this number increased to 31 inefficient provinces in 2018. Another finding is that regional splitting, GRDP per capita, population density, and fiscal capacity significantly impact local governments' efficiency. As inefficient provinces need to improve their efficiency, this study recommends that local governments focus on these four independent variables to strengthen their efficiency.